2016
DOI: 10.1007/s40722-016-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Linear diffraction analysis for optimisation of the three-float multi-mode wave energy converter M4 in regular waves including small arrays

Abstract: A general frequency domain dynamic model based on the DIFFRACT code has been developed to predict the motion and power generation of the three-float multimode wave energy converter M4, modelled as a two-body problem. The machine has previously been shown experimentally and numerically to have broad-band high capture widths for the range of wave periods typical of offshore sites. The float sizes increase from bow to stern; the bow and mid float are rigidly connected by a beam and the stern float is connected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The capture width ratio is a significant parameter to evaluate the power capture ability of a WEC. In the study of the raft-type-like WEC M4, Sun et al [22,23] normalized the capture width by wavelength to obtain the capture width ratio. Here, we also adopt the same definition, since this definition of the capture width ratio enables a comparison with theoretical maxima, e.g., 3/2π in heave and pitch and/or surge for a point absorber [28] and 4/3π for a slender two-raft WEC [29].…”
Section: Power Capture Abilitymentioning
confidence: 99%
“…The capture width ratio is a significant parameter to evaluate the power capture ability of a WEC. In the study of the raft-type-like WEC M4, Sun et al [22,23] normalized the capture width by wavelength to obtain the capture width ratio. Here, we also adopt the same definition, since this definition of the capture width ratio enables a comparison with theoretical maxima, e.g., 3/2π in heave and pitch and/or surge for a point absorber [28] and 4/3π for a slender two-raft WEC [29].…”
Section: Power Capture Abilitymentioning
confidence: 99%
“…The constraints between floats and beams can be categorised into two types: rigid connections (at "C1", "C2" and "C3") and a hinge (at "hinge O"). For rigid connections, the form of the constraint matrix D can be found in Sun et al (2011) and the corresponding constraint matrix for the hinge connection can be found in Sun et al (2016). When the PTO at "hinge O" in Fig.…”
Section: Numerical Model 21 Linear Multi-body Dynamic Modelmentioning
confidence: 99%
“…The mid and stern floats have hemispherical and rounded bases giving negligible drag losses. This has been modelled effectively for operational conditions using linear diffraction theory in the time domain (Stansby et al 2015a(Stansby et al , 2016 and the frequency domain (Eatock Taylor et al 2015;Sun et al 2016). Eatock Taylor et al provided a general structural model based on dynamic substructuring and hydrodynamic finite element analysis assuming that the floats act in isolation giving good predictions of experimental results for response and power for longer wave periods, accounting for drag effects with flat-based floats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations